IMPLEMENTASI PERDA KOTA MEDAN NOMOR 10 TAHUN 2021 TERHADAP PENGUTIPAN SUMBANGAN DALAM PERSPEKTIF SIYASAH DUSTURIYAH - Rachma Syarina Aatifa; Mhd Yadi Harahap (JAS : Jurnal Ahwal Syakhshiyyah, 2025)
This study aims to examine the implementation of Medan City Regional Regulation Number 10 of 2021 regarding the collection of public donations, both those conducted with official permission and those without legal authorization. Using a normative-empirical method and a juridical-sociological approach, the research combines statutory analysis with empirical data obtained from interviews with the Social Service Office of Medan City and three legal charitable institutions: Lazpersis Foundation (Medan Sunggal), Dompet Dhuafa Muhammadiyah (Medan Tembung), and Al-Bukhari Mosque (Medan Johor). The findings show that the regulation provides a legal foundation to restrict unauthorized donation activities that tend to lack transparency and misuse public trust. In contrast, licensed institutions demonstrate accountable and lawful practices aligned with maqāṣid al-sharī‘ah, such as supporting orphans, educational scholarships, and places of worship. From the perspective of siyāsah dustūriyyah, this regulation affirms the state’s responsibility to uphold public benefit (maṣlaḥah ‘āmmah) and social order through just and ethical governance. Keywords: Medan Regulation, Public Donation, Siyāsah Dustūriyyah   Abstrak Penelitian ini bertujuan untuk menganalisis implementasi Peraturan Daerah Kota Medan Nomor 10 Tahun 2021 terhadap praktik pengutipan sumbangan di ruang publik, baik yang dilakukan oleh lembaga berizin maupun oleh pihak tanpa izin resmi. Penelitian ini menggunakan metode normatif-empiris dengan pendekatan yuridis sosiologis, yang mengombinasikan kajian peraturan perundang-undangan dengan data lapangan melalui wawancara di tiga kecamatan, yakni Medan Johor, Medan Tembung, dan Medan Sunggal, serta Dinas Sosial Kota Medan. Hasil penelitian menunjukkan bahwa perda ini telah efektif dalam memberikan kerangka hukum untuk membatasi praktik pengumpulan sumbangan tanpa izin yang tidak akuntabel. Lembaga seperti Yayasan Lazpersis, Dompet Dhuafa Muhammadiyah, dan Masjid Al-Bukhari telah menunjukkan tata kelola sumbangan yang sah, transparan, dan sesuai prinsip maqāṣid al-syarī‘ah. Perspektif siyasah dusturiyah menegaskan peran negara dalam menjaga ketertiban umum dan mencegah kemudaratan publik melalui regulasi yang adil dan maslahat. Kata Kunci: Perda Kota Medan, Pengutipan Sumbangan, Siyasah Dusturiyah